Sustainability of additive-doped biodiesel: Analysis of its aggressiveness toward metal corrosion - Fazal, M.A.; Suhaila, N.R.; Haseeb, A.S. Md. Abdul; Rubaiee, Saeed (Elsevier, 2018)
The recent shortage of fossil fuel sources and the growing environmental concerns have considerably affected the necessity to search for alternative energy sources. The tremendous increase in energy demands in the transportation and industrial sectors has strengthened efforts to identify sustainable alternative fuel sources. In this regard, biodiesel can be considered a promising substitute for diesel. However, biodiesel is corrosive when it comes in contact with metals. The present study aims at investigating the sustainability of additive-doped biodiesel upon exposure of copper-based materials. A static immersion test was conducted at room temperature (25 °C–27 °C) for 2160 h. The metals used in the experiment were copper, leaded bronze, and phosphorous bronze. The investigated fuel was 100% palm biodiesel without and with additives (500 ppm), including tert-butylamine, benzotriazole, propyl gallate, pyrogallol, and butylated hydroxytoluene. The corrosion rate of the metals was determined at the end of the experiment via weight loss measurement. The metals were further characterized via scanning electron microscopy, energy-dispersive spectroscopy, and X-ray diffraction analysis. Results showed that the corrosion rate of copper was considerably higher than those of the other metals. X-ray diffraction analysis indicated the presence of copper carbonate and cupric oxide on the copper surface that was exposed to biodiesel. The occurrence of these compounds could be attributed to the high concentrations of carbon dioxide and oxygen in the biodiesel when additive was absent. Gas chromatography–mass spectrometry data showed that the unsaturated molecules in biodiesel could reduce the sustainability of metals upon exposure to biodiesel. However, metal surface degradation was significantly reduced in the presence of additives. In particular, benzotriazole and tert-butylamine considerably improved the sustainability of biodiesel by limiting metal surface degradation.